Mergers between regulated firms with unknown efficiency gains - Raffaele Fiocco; Gongyu Guo (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2014)
In an industry where regulated firms interact with unregulated suppliers, we investigate the welfare effects of a merger between regulated firms when cost synergies are uncertain before the merger and their realization becomes private information of the merged firm. The optimal merger policy trades off potential cost savings against regulatory distortions from informational problems. We show that, as a consequence of this trade-off, more intense competition in unregulated segments of the market induces a more lenient merger policy. The regulated firms' diversification into a competitive segment of the market can lead to a softer merger policy when competition is weaker.
urn:nbn:de:bvb:19-epub-20875-8
Keywords: D82; L43; L51; 330; asymmetric information; competition; efficiency gains; mergers; regulation